Decreasing Spatial Variability of Individual Watershed Areas by Revascularization Therapy in Patients With High‐Grade Carotid Artery Stenosis. Issue 6 (18th June 2021) - Schmitzer, Lena; Sollmann, Nico; Kufer, Jan; Kallmayer, Michael; Eckstein, Hans‐Henning; Zimmer, Claus; Preibisch, Christine; Kaczmarz, Stephan; Göttler, Jens
Abstract : Background: Carotid artery stenosis can impair cerebral hemodynamics especially within watershed areas (WSAs) between vascular territories. WSAs can shift because of collateral flow, which may be an indicator for increased hemodynamic implications and hence higher risk for ischemic stroke. However, whether revascularization treatment can reverse the spatial displacement of individual WSAs (iWSAs) and impaired hemodynamics remains unknown. Hypothesis: That iWSAs spatially normalize because of hemodynamic improvement resulting from revascularization treatment. Study Type: Prospective. Population: Sixteen patients with unilateral, high‐grade carotid artery stenosis confirmed by duplex ultrasonography and 17 healthy controls. Field strength/Sequences: A 3 T‐magnetization‐prepared rapid acquisition gradient echo (MPRAGE), gradient‐echo echo planar dynamic susceptibility contrast (DSC), and fluid‐attenuated inversion recovery (FLAIR) sequences. Additionally, contrast‐enhanced 3D gradient echo magnetic resonance angiography (MRA) and diffusion‐tensor imaging (DTI) spin‐echo echo planar imaging were performed. Assessment: iWSAs were delineated by a recently proposed procedure based on time‐to‐peak maps from DSC perfusion MRI, which were also used to evaluate perfusion delay. We spatially compared iWSAs and perfusion delay before and after treatment (endarterectomy or stenting). Additionally, the Circle of Willis collateralization status was evaluated, and basic cognitive testing was conducted. Statistical Tests: Statistical tests included two‐sample t‐tests and Chi‐squared tests. A P value < 0.05 was considered to be statistically significant. Results: After revascularization, patients showed a significant spatial shift of iWSAs and significantly reduced perfusion delay ipsilateral to the stenosis. Spatial shift of iWSA ( P = 0.007) and cognitive improvement ( P = 0.013) were more pronounced in patients with poor pre‐existing collateralization. Controls demonstrated stable spatial extent of iWSAs ( P = 0.437) and symmetric perfusion delays between hemispheres over time ( P = 0.773). Data Conclusion: These results demonstrate the normalization of iWSA and impaired hemodynamics after revascularization in patients with high‐grade carotid artery stenosis. Level of Evidence: 2 Technical Efficacy: Stage 2